(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
An extreme example of prejudice and discrimination in India may be found in the form of violentcrimes committed by members of higher castes against members of historically oppressed groups knownas Scheduled Castes and Scheduled Tribes (SCST). In this study, we evaluate whether or not there is acorrelation between changes in the relative material standards of living between the SCST and uppercastes, as assessed by consumer expenditures, and changes in the incidence of crimes committedagainst SCST. We establish a positive correlation between crimes and expenditures of SCST vies thehigher castes by using official district level crime data for the period 2001-10. This suggests that awidening of the gap between groups is connected with a drop in caste-based crimes. In addition, itappears that the upper castes are the ones driving this impact, as they are the ones reacting to changesin the status quo. The findings are not sensitive to modifications made to the modelling assumptions orthe specifications.